Effects of plasma actuator on flow over an airfoil - Ang, Edwin Wen Jun (2015)
This project investigates the feasibility of using Nanosecond Pulse Dielectric Barrier Discharge Plasma Actuator (NS-DBD) to replace existing flow controlling devices. The advantages of NS-DBD include simpler in design, light weight, present no parasite drag and allows active control with zero reaction time. Two features of flow control are investigated: delaying flow separation and controlling of lift generated. A NACA 0015 airfoil with plasma actuator installed at the surface was tested in an opened-loop wind tunnel at Re=106k and 212k and the aerodynamic forces were measured using a six-axis force/torque sensor. Hot-wire anemometry had first been conducted to identify the characteristic frequencies of the shear layer and wake vortices without excitation, however the frequency of the former could not be identified in this project. For the experiments pertaining to flow separation control, the actuator was placed at the leading edge and post-stall angle of attack (AOA) of 15⁰ and 18⁰ were set. It was found that the maximum lift increments (up to 75%) were recorded when the excitation frequencies were near the characteristics frequencies of the wake vortices (F+≈0.6). Greater drag reductions (up to 36%) were recorded with the increase in excitation frequencies (F+≈2 to 4). As the characteristic frequency of the shear layer vortices was not found, the current project could not verify the mechanism responsible for the drag reduction. Also, burst mode excitation was employed to combine the high lift increment and drag reduction effects of the low and high excitation frequencies. Despite initial experimental success of using burst mode, the results could not be repeated, and further attempts to repeat the experiment was hindered by electromagnetic interference (EMI). Comparison with existing devices that delay flow separation showed that NS-DBD exceed the performances of both vortex generators and slat. For experiments conducted to investigate lift control, the actuator was placed at x/c=0.5 and 0.75 on pressure and suction side; pre-stall AOA of 0⁰ to 12⁰ were set. However, only the actuator placed at x/c=0.5 on the pressure side produced significant changes in lift. The lift increased by up to 15% at AOA of less than 5⁰ and decreased by up to 10% at AOA of more than 5⁰. At 5⁰ AOA, the increment or reduction of lift depended on the excitation frequency; lift increases at low frequency and decreases as frequency increases.